Linguocultural classification of expressiveness and speech-cultural evaluation in English and Uzbek online newspapers - Madiyarov , Babur Allambergenovich (The Lingua Spectrum, 2026)
This article investigates the linguocultural mechanisms underlying expressive language and speech-cultural evaluation in English and Uzbek online news discourse. Online newspapers constitute a distinctive genre in which the norms of journalistic objectivity converge with evaluative and emotionally charged language strategies characteristic of digital communication. Drawing on a corpus of two hundred texts comprising news reports, opinion pieces, and editorial commentaries collected from four English-language and four Uzbek-language online outlets the study applies a comparative linguocultural framework to classify expressive and evaluative units identified in the texts. The analysis reveals systematic differences in the density, structural realisation, and culturally grounded functions of expressive language across the two corpora. These differences reflect divergent journalistic traditions, rhetorical conventions, and sociolinguistic norms. In each cultural context, expressive resources are shaped by specific value systems and communicative norms. The findings carry significant theoretical and practical implications for cross-cultural media literacy, translation practice, and contrastive linguistics.